Role of the NO-cGMP pathway in the muscarinic regulation of the L-type Ca(2+) current in human atrial myocytes - Vandecasteele, Grégoire (Blackwell Science Inc, 1998)
1. The whole-cell patch-clamp technique was used to examine the participation of nitric oxide synthase (NOS) and soluble guanylyl cyclase in the muscarinic regulation of the L-type Ca(2+) current (I(Ca)) in freshly isolated human atrial myocytes. 2. Acetylcholine (ACh, 1 μM) decreased basal I(Ca) by 39.1 ± 5.5 % (n= 8) under control conditions, and by 38.0 ± 6.1 % (n= 6) in the presence of 1H-[1,2,4]oxadiazolo[4,3-a]quinoxaline-1-one (ODQ, 10 μM), a potent guanylyl cyclase inhibitor, and N(G)-monomethyl-L-arginine (L-NMMA, 1 mM), a competitive NOS inhibitor. L-NMMA alone had no effect on I(Ca), whilst ODQ increased I(Ca) in 50 % of the cells. 3. The accentuated antagonism of ACh on I(Ca), i.e. its ability to antagonize the stimulatory effect of β-adrenergic agonists and, by extension, of other cAMP-elevating agents, was examined after the current was stimulated by either the β-adrenergic agonist isoprenaline (Iso) or serotonin (5-HT). ACh (100 nM or 1 μM) completely blocked the stimulatory effects of 10 nM Iso or 10 nM 5-HT on I(Ca). 4. Extracellular application of Methylene Blue (MBlue, 10 μM), a guanylyl cyclase inhibitor, antagonized the inhibitory effect of 1 μM ACh on Iso- or 5-HT-stimulated I(Ca). However, this effect was overcome by a 100-fold higher ACh concentration and was not mimicked by an intracellular application of MBlue. 5. Inhibition of NOS and soluble guanylyl cyclase activities by addition of ODQ (10 μM) and L-NMMA (1 mM) to both extracellular and intracellular solutions, or by a 2 h pre-incubation of the cells with these inhibitors, modified neither the Iso (10 nM) response nor the inhibitory effect of ACh (100 nM or 1 μM) on Iso-stimulated I(Ca). 6. Extracellular application of the NO donor SNAP (S-nitroso-N-acetyl-d,l-penicillamine) at 100 nM produced a stimulatory effect on I(Ca) in control conditions. This stimulatory effect was abolished by intracellular MBlue (20 μM) or by intracellular and extracellular application of ODQ (10 μM) in combination with L-NMMA (1 mM). 7. We conclude that the NO-cGMP pathway does not contribute significantly to the muscarinic regulation of I(Ca) in human atrial myocytes.